Upaya Meningkatkan Pemahaman Konsep Biologi Menggunakan Media Charta, Model, dan Power Point Pada Siswa Kelas XI-IPA SMA Dr Musta'in Romly Tahun Pelajaran 2018/2019 - wahid (FKIP, Universitas Billfath Lamongan, 2020)
This study aims to improve understanding of the concept of biology using chart media, models, and power points in class XI-IPA students for the 2018/2019 academic year. This research is a type of action research designed in the form of a cycle. Each cycle consists of planning, implementing, self-reflection. From each cycle that has been implemented, the results obtained are: the completeness of student learning outcomes until cycle III with classical learning outcomes reaching 90%. Meanwhile, the teacher's ability to manage learning using chart media, models, and power points in each cycle has increased. This has a positive impact on student achievement, which can be shown by the increase in the average score of students in each cycle which continues to increase. In terms of teacher and student activities in learning, it can be seen from the activities of teachers that appear including activities to guide and observe students in doing power point activities / finding concepts, explaining / training using tools, giving feedback / evaluation / question and answer where the percentage for the above activities is sufficient big.